Terminology of House and Household Items in Valjevska Podgorina - Štrbac, Gordana R.; Štrbac, Snežana R. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper analyses groups of terms referring to house and household items in Valjevska Podgorina, i.e. the words that denote realia related to the traditional housing and dwelling, which represent one of the most significant aspects of intangible cultural heritage. The terms are classified thematically, in accordance with the type of realia they denote and the domain of use of the realia in question. The analysis of terminology related to house and household items in Valjevska Podgorina reveals two lexical principles, which also reflect the way of thinking as they are relevant to the way in which people understand and organize reality around them. They refer to the two basic hypernym-hyponym relations, known as taxonomy and meronymy in linguistics. They are presented by using the examples of lexical subgroups “house and its parts” and “tableware and food related items”.